2006
DOI: 10.1021/ma0606354
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Isotactic Propylene−Hexene Copolymers:  The Trigonal Form of Isotactic Polypropylene

Abstract: A study of the structure of isotactic propylene-hexene random copolymers, prepared with singlecenter metallocene catalysts, is reported. For low concentrations of hexene comonomeric units, up to nearly 10 mol %, copolymers crystallize in the R form of isotactic polypropylene. Copolymers with hexene contents higher than 10 mol % crystallize in a new polymorphic form that melts at nearly 50 °C. The hexene units are partially included in both crystals of R form and of the new form. The crystallization of the new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
222
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(233 citation statements)
references
References 19 publications
11
222
0
Order By: Relevance
“…Density values in these CiPH correlate rather well with those reported in the literature for analogous copolymers. [19] On the other hand, Figure 1 shows the WAXD profiles at room temperature for the different CiPOD copolymers and that found in the iPP homopolymer for comparison reasons. It can be observed that the profiles of the neat iPP and CiPOD1.0 and CiPOD2.3 copolymers exhibit the five main diffractions [(110), (040), (130), (111), and (130, 041) planes] characteristic of the a monoclinic iPP crystalline modification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Density values in these CiPH correlate rather well with those reported in the literature for analogous copolymers. [19] On the other hand, Figure 1 shows the WAXD profiles at room temperature for the different CiPOD copolymers and that found in the iPP homopolymer for comparison reasons. It can be observed that the profiles of the neat iPP and CiPOD1.0 and CiPOD2.3 copolymers exhibit the five main diffractions [(110), (040), (130), (111), and (130, 041) planes] characteristic of the a monoclinic iPP crystalline modification.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] An interesting finding is that a crystal structure neither resembles those of the well-known a, b, and g phases of isotactic poly(propylene) (iPP) nor that of isotactic poly-1-hexene has been uncovered in copolymers of propylene-1-hexene (CiPH) with relatively high molar contents in 1-hexene (>10%), crystallized at moderate rates and annealed at room temperature. [17][18][19] On the other hand, specimens of low molecular weight CiPH copolymers with relatively low 1-hexene molar fractions (up to a 5 mol-%), prepared by a fast cooling from the molten state, [20] show a much easier formation of mesomorphic structures similar to those observed in either effective-quenched or stretched iPP. [21,22] Moreover, the effect of comonomer size on the final properties is expected to be more dramatic in the case of propylene copolymers, although contradictory results have been reported in the open literature.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated cooling rates (>100°C/s) inhibit the stable monoclinic modification in favour of a mesomorphic form [1,12]. Two other modification (δ [13] and ∊ [14]) have been reported in literature, but they are outside the scope of this work.…”
Section: Introductionmentioning
confidence: 83%
“…The corresponding values are shown in Table 3. 7 The crystal size in the (110) direction, lc (110), has been also determined from the width at half height of the corresponding diffraction, calculated through Scherrer equation. [43] These values are also indicated in Table 3.…”
Section: Experimental Partmentioning
confidence: 99%
“…In addition, a new trigonal form has been described in the case of copolymers of iPP with high contents of 1-hexene or 1-pentene as comonomers. [5][6][7][8][9][10] Moreover, a kind of mesomorphic form has been found to appear not only in homopolymer but also in different random copolymers, with comonomers such as ethylene, 1-butene, 1-pentene and other -olefin copolymers. [11][12][13][14] Among the different paths for modifying the ability to crystallize the iPP and the type of polymorph desired, this paper focuses on the introduction of comonomer units.…”
Section: Introductionmentioning
confidence: 99%